2003
DOI: 10.1093/carcin/bgg192
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane: a naturally occurring mammary carcinoma mitotic inhibitor, which disrupts tubulin polymerization

Abstract: Sulforaphane (SUL), an isothiocyanate found in broccoli and other cruciferous vegetables, has been shown to induce phase II detoxification enzymes, inhibit chemically induced mammary tumors in rats, and more recently to induce cell cycle arrest and apoptosis in cancer cells of the colon. Here, we provide evidence that SUL also acts as a breast cancer anti-proliferative agent. The BALB/c mouse mammary carcinoma cell line F3II was treated with SUL at concentrations up to 15 microM and examined for markers of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
129
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 51 publications
10
129
0
Order By: Relevance
“…On the other hand, the SFN-mediated G 2 -M phase cell cycle arrest is rapid and evident as early as 4 h posttreatment. The G 2 -M phase cell cycle arrest by SFN treatment at concentrations within the range used in the present study has also been observed in other cellular systems including HT29 human colon cancer cell line (15), F3II mouse sarcomatoid mammary carcinoma cell line (17), PC-3 and DU145 human prostate cancer cells (19,20), and human benign prostate hyperplasia epithelial cell line BPH-1 (23). In contrast, previous studies by Chiao et al (46) have documented a G 1 phase cell cycle arrest in LNCaP cells following a 24-h exposure to 3 and 9 Amol/L SFN.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…On the other hand, the SFN-mediated G 2 -M phase cell cycle arrest is rapid and evident as early as 4 h posttreatment. The G 2 -M phase cell cycle arrest by SFN treatment at concentrations within the range used in the present study has also been observed in other cellular systems including HT29 human colon cancer cell line (15), F3II mouse sarcomatoid mammary carcinoma cell line (17), PC-3 and DU145 human prostate cancer cells (19,20), and human benign prostate hyperplasia epithelial cell line BPH-1 (23). In contrast, previous studies by Chiao et al (46) have documented a G 1 phase cell cycle arrest in LNCaP cells following a 24-h exposure to 3 and 9 Amol/L SFN.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, the immunofluorescence microscopy of SFN-treated LNCaP cells after staining with 4 ¶,6-diamidino-2-phenylindole as well as analysis of Ser 10 phosphorylation of histone H3 confirms mitotic arrest in our model. The SFN-mediated mitotic arrest is not restricted to the LNCaP cell line because similar response has been described previously in F3II mouse mammary carcinoma cells (17). Exposure of synchronized F3II cells to 15 Amol/L SFN results in elevated numbers of prophase/prometaphase mitotic figures, indicating progression beyond G 2 and arrest early in mitosis (17).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A recent study showed that SFN treatments can disrupt tubulin polymerization and spindle assembly, which in turn caused mitotic arrest (22). We demonstrated here that ITCs inhibit tubulin polymerization and disrupt microtubule networks in the same relative order of potency, providing evidence for models in which ITC binding to tubulin disrupts microtubule formation, which may then provoke cell cycle arrest and apoptosis.…”
Section: Discussionsupporting
confidence: 63%
“…It is conceivable that the structure of individual ITC compounds may influence their binding preferences as it dictates hydrophobicity, size, shape, and electrophilicity. The selective interactions obtained with intracellular proteins were suggested by previous studies in which ITCs were shown to inhibit preferentially, presumably via binding to enzymes, specific cytochrome P450 isozymes, depending on their structures (22,(23)(24)(25)(26). A recent study showed that two SFN derivatives, SFN-N-acetylcysteine and SFN-cysteine, were effective histone deacetylase (HDAC) inhibitors, whereas the SFN parent compound had little effect (27).…”
Section: Discussionmentioning
confidence: 96%